2021
DOI: 10.3389/fphar.2021.620635
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Metamizole (Dipyrone) and Naproxen on Renal Function and Prostacyclin Synthesis in Salt-Depleted Healthy Subjects - A Randomized Controlled Parallel Group Study

Abstract: Aim: The objective was to investigate the effect of metamizole on renal function in healthy, salt-depleted volunteers. In addition, the pharmacokinetics of the four major metamizole metabolites were assessed and correlated with the pharmacodynamic effect using urinary excretion of the prostacyclin metabolite 6-keto-prostaglandin F1α.Methods: Fifteen healthy male volunteers were studied in an open-label randomized controlled parallel group study. Eight subjects received oral metamizole 1,000 mg three times dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The use of omeprazole prevented polymyxin E-induced nephrotoxicity in a rat model and was used in some horses concurrently to PolyB [32]. Metamizol on the other hand is reported to cause acute kidney injury in a low number of human patients and might have also influenced renal function in horses concurrently treated with this antipyretic drug in the present study [33]. No data exist on the influence of other concurrently used drugs such as anti-inflammatory, anticoagulant, and gastroprotective substances on the pharmacokinetics, therapeutic and side effects of PolyB.…”
Section: Discussionmentioning
confidence: 59%
“…The use of omeprazole prevented polymyxin E-induced nephrotoxicity in a rat model and was used in some horses concurrently to PolyB [32]. Metamizol on the other hand is reported to cause acute kidney injury in a low number of human patients and might have also influenced renal function in horses concurrently treated with this antipyretic drug in the present study [33]. No data exist on the influence of other concurrently used drugs such as anti-inflammatory, anticoagulant, and gastroprotective substances on the pharmacokinetics, therapeutic and side effects of PolyB.…”
Section: Discussionmentioning
confidence: 59%
“…Although one study reported that short-term use of metamizole did not affect renal function in healthy adults [56], little is known about the nephrotoxic potential of metamizole. In view of its growing popularity, it is important to further investigate the safety profile of metamizole in future studies, especially in older adults with comorbidities and comedications.…”
Section: Original Articlementioning
confidence: 99%
“…Other possible mechanisms that try to explain the metamizole effects involves the stimulation of cannabinoid receptors, action on the serotonergic and noradrenergic systems of descending pathways, or, even, action on the protein kinase c-dependent pathway [11].…”
Section: Introductionmentioning
confidence: 99%